TRANSFORMATIVE LEADERSHIP AS A CREATIVE HUMAN RESOURCE DEVELOPMENT MODEL - Adelia Kusmiaji; Ajeng Ayu Lestari; Asni Khoirunisa; Silma Mausuli; Syaiful Anwar (OIKONOMIA: Journal of Economics and Management Science, 2024)
Transformative leadership is a promising paradigm for developing creative human resources. Effective leadership needs to provide direction to all employees in an effort to achieve organizational goals. Transformational leadership plays a crucial role in improving employee performance, it is proven that leaders who have a high transformational attitude will provide a positive example to their employees. This study aims to develop a conceptual theory of transformational leadership as a foundational framework for the development of creative human resources within organizations. This study conducts a comprehensive analysis of various leadership styles, including transformational, transactional, and charismatic leadership, along with the concepts of innovation and creativity. The findings of the study demonstrate that transformational leadership plays a pivotal role in fostering creativity among human resources by emphasizing credibility and the cultivation of novel and unique ideas